Pengaruuh Online Customer Review Dan Promosi Menggunakan Aplikasi Titok Terhadap Keputusan Pembelian Produk Kecantikan Implora Pada Marketplace Shopee - Aulia Hasanah; Kosasih Kosasih (Peneliti.net, 2022)
This study aims to determine the effect of online customer reviews and promotions using the tiktok application on purchasing decisions for implora beauty products in the shopee market place. The method used in this study uses a verification method with a quantitative approach, the sample used is 215 by using a non-probability sampling method. The sampling technique that will be used is purposive sampling, which is a sampling technique carried out with certain considerations. The data analysis technique used is path analysis with partial hypothesis testing and simultaneous hypothesis testing. The result of this research is that there is a correlation between the online costomer review variable and the pro, osi of 0.890 which is in the very good category. There is a partial influence of Online Customer Review on Purchase Decisions of 0.638 or 63.8%. Promotion using Tiktok Application on Purchase Decision is 0.170 or 17%. Together, the Online Customer Review and Promotion Using Tiktok Applications on Purchase Decisions have a simultaneous influence of 0.808 or 80.8% while the remaining 19.2% is the contribution of other variables (£) which were not examined in this study.